Efficacy of virtual reality exposure therapy and eye movement desensitization and reprocessing therapy on symptoms of acrophobia and anxiety sensitivity in adolescent girls: A randomized controlled trial - Azimisefat, Parisa; de Jongh, Ad; Rajabi, Soran; Kanske, Philipp; Jamshidi, Fatemeh (Frontiers in Psychology, 2022)
BACKGROUND: Acrophobia is a specific phobia characterized by a severe fear of heights. The purpose of the present study was to investigate the efficacy of two therapies that may ameliorate symptoms of acrophobia and anxiety sensitivity, i.e. virtual reality exposure therapy (VRET) and eye movement desensitization and reprocessing (EMDR) therapy with a Waiting List Control Condition (WLCC). METHODS: We applied a three-armed randomized controlled pre-post-test design with 45 female adolescent students. Students who met DSM-5 criteria for acrophobia were randomly assigned to either VRET (N=15; Mage=17.26; SD=1.32), EMDR (N=15; Mage=17.15; SD=1.57), or a WLCC (N=15; Mage=17.50; SD=1.26). The study groups were evaluated one week before the intervention and one week after the last intervention session regarding symptoms of acrophobia (Severity Measure for Acrophobia) and anxiety sensitivity (Anxiety Sensitivity Index). RESULTS: The data showed that both the application of VRET and EMDR therapy were associated with significantly reduced symptoms of acrophobia (d = 1.03 for VRET and d = 1.08 for EMDR) and anxiety sensitivity (d = 1.15 for VRET and d = 1.13 for EMDR) in comparison to the Waiting List. LIMITATIONS: The sample consisted only of adolescent women. Due to the recognizable differences between the two interventions, the therapists and the participants were not blind to the conditions. CONCLUSION: The results suggest that both VRET and EMDR are interventions that can significantly improve symptoms of acrophobia and anxiety sensitivity in female adolescents.